PROBLEMS AND APPROACHES IN FINANCING SOCIAL-PEDAGOGICAL ACTIVITIES AT THE MUNICIPAL LEVEL: PROBLEMS AND APPROACHES IN FINANCING SOCIAL-PEDAGOGICAL ACTIVITIES AT THE MUNICIPAL LEVEL - Niyazi, Berivan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
This paper examines the significance of social-pedagogical work at the local level as a tool for support, prevention, and social integration of vulnerable groups. Social pedagogues perform a variety of functions that enable them to have a positive impact on the social environment and the quality of life within the community. At the same time, challenges such as limited resources, a shortage of qualified personnel, and the complexity of social problems are identified. The conclusion emphasizes that social-pedagogical work is a key factor in building active, cohesive, and sustainable communities, as well as in promoting equal access to education and social services.